The effect of the surface patterning by ion beam irradiation on the Ag directional outflow in Ag/AlN nano-multilayers. (April 2023) - Druzhinin, A.V.; Cancellieri, C.; Hauert, R.; Klyatskina, E.A.; Khrapova, N.N.; Mazilkin, A.A.; Straumal, B.B.; Janczak-Rusch, J.
Abstract: Surface templating of nano-multilayers is a promising step for the advanced industrial application of these nanomaterials. In the present work, the effect of focused ion beam modification of Ag/AlN nano-multilayer near-surface region on the Ag surface outflow is revealed. Surface patterning by ion beam irradiation leads to the formation of a higher amount of Ag crystals in relation to the intact surface region. Heat treatment initiates grooving of Ag grain boundaries, resulting in the formation of channels in the nano-multilayer volume. These channels act as pathways for mass transport of Ag to the film surface. Ion bombardment creates regions of high concentration of non-equilibrium defects, which locally increase the driving force for grooving and channeling, thereby promoting creation of more pathways for Ag surface migration. The obtained experimental results indicate that surface modification by focused ion beam can be used for production of nano-multilayers with designed templates of surface outflow. Highlights: Ag crystals are formed on the nano-multilayer surface upon high-vacuum annealing. The HeFIB surface modification results in a higher density of Ag crystals. Annealing induces formation of channels in the nano-multilayer volume.